Vitamin-C-enabled reduced graphene oxide chemistry for tuning biofilm phenotypes of methylotrophs on nickel electrodes in microbial fuel cells. (March 2020) - Islam, Jamil; Chilkoor, Govinda; Jawaharraj, Kalimuthu; Dhiman, Saurabh Sudha; Sani, Rajesh; Gadhamshetty, Venkataramana
Graphical abstract: Highlights: 3D reduced graphene oxide/nickel electrode for growth of methylotrophic biofilms. Graphene oxide reduction by vitamin C yields superhydrophilic 3D nickel electrodes. 3D rGO/Ni electrode yields 220 fold higher power density in methanol-fed MFCs. Microscopic analysis of electroactive Rhodobacter Sphaeroides spp. Abstract: This study reports the use of multi-layered reduced graphene oxide (rGO) coating on porous nickel foam (NF) electrodes for enhancing biofilm growth of Rhodobacter Sphaeroides spp fed with methanol in microbial fuel cells (CH3 OH-MFCs). Electrochemical methods were used to assess the methylotrophic activity on rGO/NF electrodes. The power density and current density offered by rGO/NF (1200 mW m −2 and 680 mA m −2 ) were 220-fold and 540-fold higher compared to bare NF (5.50 mW m −2 and 1.26 mA m −2 ), respectively. Electrochemical impedance spectroscopy results show that rGO/NF suppresses charge transfer resistance to CH3 OH oxidation by 40-fold compared to the control. This improved performance is due to the ability of rGO coatings to decrease the wetting contact angle (improve the hydrophilicity) of NF from 128 0 to 0 0 . A preliminary cost analysis was carried out to assess the viability of rGO/NF electrodes via vitamin-C-enabled graphene oxide chemistry for CH3 OH-MFCs applications.